Documentation in the history, methods of preparation, and microbiological quality of Pampanga's Suman Tili (whole kernel glutinous rice cake) - Pineda, Ryan Nikkole Bondoc (College of Home Economics, University of the Philippines Diliman, 2019)
The study aimed to document the history, methods of preparation, and microbiological quality of suman tili, a well-known rice cake from the province of Pampanga, Philippines. The arrival of the Chinese in Pampanga in 1603 have influenced its creation. Suman tili is a whole kernel rice cake made from glutinous rice, coconut milk/cream, sugar, and packed in cigar banana leaf. Its appearance is that of a long, rectangular cylinder, with tapered sides. Desirable sensorial characteristics include a soft and sticky texture with a good balance of flavour. The method of preparing suman tili include cooking of glutinous rice in coconut milk, cooking of coconut cream/milk to produce latik (browned coagulated coconut milk), mixing of cooked glutinous rice with latik and sugar, wrapping in young banana leaves, and steaming. Documentation on the weights and dimensions of suman tili products showed average weights ranging from 87-93 grams and 66-81 grams for suman tili with banana leaf covering and without the packaging, respectively. The recorded length for suman tili with banana leaf covering (and without covering) ranged from 147-160 millimetres (140-154mm), width ranging from 24-37mm (25-30mm), and thickness of 19-20mm (16-18mm). The microbiological tests for the raw materials showed that two out of three suppliers generally had lower microbial count. The microbiological counts both showed an increase and decrease after steaming of the suman tili in relation to the microbial count of the finished product before steaming. The results also showed that aerobic plate count and B. cereus count of unsteamed and steamed suman tili were satisfactory based on different regulatory standards for ready-to-eat foods but were unsatisfactory for S. aureus and E. coli count. The microbiological load of suman tili was greatly influenced xii by the high initial microbial load of the raw materials and improper handling during production. Overall, the poor microbiological quality of both the raw materials and finished product are mainly associated with poor sanitation in work stations, extensive handling, and lack of knowledge regarding good manufacturing and hygienic practices. It was recommended to educate and train suman tili manufacturers and as well as merchants of the raw materials with regard to good manufacturing and hygienic practices to help improve the microbiological quality of the finished product.